2021
DOI: 10.1111/desc.13133
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation in the face of adversity: Decrements and enhancements in children's cognitive control behavior following early caregiving instability

Abstract: Cognitive control is typically described as disrupted following exposure to early caregiving instability. While much of the work within this field has approached cognitive control broadly, evidence from adults retrospectively reporting early-life instability has shown more nuanced effects on cognitive control, even demonstrating enhancements in certain subdomains. That is, exposure to unstable caregiving may disrupt some areas of cognitive control, yet promote adaptation in others. Here, we investigated three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
52
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(61 citation statements)
references
References 59 publications
(89 reference statements)
6
52
1
Order By: Relevance
“…Findings indicated that adults who grew up in socioeconomically disadvantaged and/or chaotic households tended to show improved cognitive shifting, but poorer inhibition and impulsivity, within the uncertain context. Similar findings among children have been recently reported by Fields et al (2021), who found that children who had experienced caregiving instability tended to have better cognitive flexibility, but reduced attentional control and response inhibition, compared with children who had not experienced instability in caregiving. In both of these cases, a possible interpretation is that within the context of scarcity or chaos, individuals adapt to context, with resultant improvement in task switching, but at a cost to attention and response inhibition.…”
Section: Deficits Versus Adaptationssupporting
confidence: 89%
“…Findings indicated that adults who grew up in socioeconomically disadvantaged and/or chaotic households tended to show improved cognitive shifting, but poorer inhibition and impulsivity, within the uncertain context. Similar findings among children have been recently reported by Fields et al (2021), who found that children who had experienced caregiving instability tended to have better cognitive flexibility, but reduced attentional control and response inhibition, compared with children who had not experienced instability in caregiving. In both of these cases, a possible interpretation is that within the context of scarcity or chaos, individuals adapt to context, with resultant improvement in task switching, but at a cost to attention and response inhibition.…”
Section: Deficits Versus Adaptationssupporting
confidence: 89%
“…One of the domains most consistently influenced by early-life deprivation is higher-order cognition, including executive functions. Adults and children who report growing up in more unpredictable family environments, or who experienced more family instability while growing up, tend to display reduced inhibitory control and working memory capacity, but enhanced abilities for flexibly switching between tasks or mental sets and for tracking novel environmental information, particularly when in an experimentally induced mindset of stress/uncertainty (Fields et al, 2021;Mittal et al, 2015;Young et al, 2018). Importantly, the two prospective studies of family instability (Fields et al, 2021;Mittal et al, 2015) included participants with substantial histories of deprivation (e.g., institutionalization, poverty).…”
Section: Integrating Unpredictability Into the Threat-deprivation Fra...mentioning
confidence: 99%
“…Adults and children who report growing up in more unpredictable family environments, or who experienced more family instability while growing up, tend to display reduced inhibitory control and working memory capacity, but enhanced abilities for flexibly switching between tasks or mental sets and for tracking novel environmental information, particularly when in an experimentally induced mindset of stress/uncertainty (Fields et al, 2021;Mittal et al, 2015;Young et al, 2018). Importantly, the two prospective studies of family instability (Fields et al, 2021;Mittal et al, 2015) included participants with substantial histories of deprivation (e.g., institutionalization, poverty). This suggests the intriguing possibility that when experiences of deprivation are unpredictable, the impact on at least some aspects of executive functioning (i.e., cognitive flexibility) may be mitigated.…”
Section: Integrating Unpredictability Into the Threat-deprivation Fra...mentioning
confidence: 99%
“…(2) cognitive flexibility, as reflected by the ability to shift attention between tasks; and (3) replacing older, irrelevant information from working memory with new, updated information (e.g., Fields et al, 2021;Mittal et al, 2015;Nweze et al, 2021;Young et al, 2018Young et al, , 2022. For example, Mittal and his colleagues (2015) reported that young adults who had experienced harsh and unpredictable childhoods showed deficits in inhibition (a component of executive function) but displayed enhanced abilities in task shifting (also a component of executive function) compared to people who had experienced less-harsh and more stable early environments, but only when testing was done in uncertain contexts.…”
Section: Taking Advantage Of Stress-adapted Children's Hidden Talentsmentioning
confidence: 99%